Mining from a conflicting to a collaborative activity: Review of literature - Feyen, Jan; Crespo, Patricio; Célleri, Rolando (Maskana, 2015)
This article states that the confrontational attitude between local communities pushed by lobbying groups, eventually with the support of local governments, and mining companies can be turned into a corporate communication and cooperation model. Several of the large mining companies recently adopted a corporate business model in which ample room is given to the social and economic desires of the communities living nearby mining sites. Proposed actions that contribute to a collaborative attitude are the investment of time in the setting up of a communication model, the negotiation of impact and benefit agreements, involving community members in the organization and exploitation of services and the provision of goods, training of locals in conservation and restoration techniques and related technologies, and making available infrastructure and equipment as to enable locals developing economic activities which they independently can continue after mine closure. Involving the local scientific community, eventually in association with environmentalists, in activities of monitoring, mitigation, remediation and restoration helps this sector to develop capacity which will be beneficial in educational and research related programs. Governments’ participation will culminate in a better legal framework and the development of more efficient protocols for the verification if mining is conducted in an ethical, social and environmental sound manner.